Structure and organization of children's work on the streets in Belo Horizonte, MG, Brazil - Cruz, Maria Núbia Alves; Assunção, Ada Ávila (Saúde e Sociedade, 2008)
This article analyses the organization and work practices of subjects enrolled in public programs of income transfer, focusing on the strategies developed and on the role of families in placing children and adolescents in street jobs. The qualitative method that was used applied activity observation techniques combined with simultaneous and outside work interviews. Narrative analysis was used based on categories of interest defined to answer the study hypothesis. The results show that there is a direct influence of families and the community on the performance of the activities and that the groups mobilize strategies to achieve their aims. This behavior expresses that the family and society accept and participate in the organization of children's work on the street. However, exposure to violence is not diminished by parents' participation nor by the constitution of a supposed solidarity network. Educational possibilities are not anticipated due to the work conditions, which are incompatible with the subjects' age.